Disaster Mitigation and First Aid Counseling: Building Kupuk Village Preparedness - Mujahidin, Muammar; Safitri, Dian; Aprilia, Dhea; Nurhuda, Muhammad Aldi; Muttaqin, Muhammad Azam (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
The village of Kupuk, situated in the Bungkal District of the Ponorogo Regency in East Java, is extremely vulnerable to natural disasters such as forest fires and tornadoes. The level of public awareness and readiness for this disaster must still be enhanced. This area also has natural springs, often the location of drowning accidents. To address this issue, students from Muhammadiyah University of Ponorogo participating in a community service program have created an educational video on disaster preparedness and first aid. Creating this video requires identifying disaster risks, collaborating with experts and relevant authorities, collecting in-depth information, conducting first aid simulations, professional video production, expert content validation, and distribution through social media and local community networks. This initiative's results indicate that disaster mitigation and community education play a crucial role in safeguarding communities from the threat of natural disasters. Collaboration between stakeholders and video technology has increased the community's awareness and preparedness for emergency situations. This video has the potential to serve as an illustrative model for other regions confronting comparable threats.